Regeneration of Spent Lubricant Refining Clays by Solvent Extraction - Yan-zhen Wang; Hai-long Xu; Li Gao; Meng-meng Yan; Hong-ling Duan; Chun-min Song (International Journal of Chemical Engineering)
Step-by-step solvent extraction was used to regenerate spent clay by recovering the adsorbed oil in lubricating oil refining clay. Several polar and nonpolar solvents were tested, and petroleum ether (90–120°C) and ethanol (95 v%) were selected as the nonpolar and polar solvents, respectively. The spent clay was first extracted using petroleum ether (90–120°C) to obtain ideal oil and then extracted with a mixed solvent of petroleum ether (90–120°C) and ethanol (95 v%) two or three times to obtain nonideal oil before being extracted with ethanol and water. Finally, the clay was dried at 130°C to obtain regenerated clay. The total oil recovery can be more than 99 wt% of the adsorbed oil. The recovered ideal oil can be used as lubricating base oil. Shorter storage times for spent clay produce better regeneration results. The regenerated clay can be reused to refine the lubricating base oils.